About the characteristics of «internal» and «external» epidemiological risks in the territory Rostov region - A. A. Kononenko; S. S. Vodyanitskaya (Медицинский вестник Юга России, 2020)
Objective: to identify some «internal» and «external» risks that are signifi cant for the Rostov region and calculate their quantitative characteristics.Materials and methods: materials for «internal» risks in the administrative territories of the Rostov region served materials FBUZ «Center of hygiene and epidemiology in the Rostov region» on the incidence of Crimean hemorrhagic fever (KGL) and West Nile (LSN) during the period 2004 – 2017 as a whole across the Rostov region and the slit regions, the data of the regional law «About administrative-territorial structure of Rostov region», the Results of the national census. To determine the «internal» risks, we used the guidelines developed by us «Methodology for assessing the territory of the subject of the Russian Federation on the integral indicator of population morbidity with arbovirus infections», approved by Th e decision of the Academic Council of the Rostov-on-Don anti-plague Institute of Rospotrebnadzor and approved by the Director.Results: based on the results of the ranking of the territory of the Rostov region on the incidence of KGL and LDL, the degree of epidemiological risk was assessed and «risk territories» were identifi ed for these nosologies, which can serve as a basis for risk management — making scientifi cally based management decisions. To calculate the magnitude of the «external» risk and further spread of the disease, you can use various methods to assess the probability of adverse development of the epidemiological situation under the infl uence of various risk factors. Epidemiological risk can also be characterized by multiplying the individual risk by the population exposed to risk factors.Conclusions: identifi cation and calculation of risk levels depending on risk factors will help determine the scope of management decisions, and the specifi cation of risk factors will allow you to develop specifi c measures to reduce risk.